2023
DOI: 10.3390/plants12030599
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Foliar Application of Hydrogen Peroxide on Gas Exchange, Photochemical Efficiency, and Growth of Soursop under Salt Stress

Abstract: Hydrogen peroxide at low concentrations has been used as a salt stress attenuator because it induces a positive response in the antioxidant system of plants. This study aimed to assess the gas exchange, quantum yield, and development of soursop plants cv. Morada Nova grown with saline water irrigation and foliar hydrogen peroxide application. The experiment was carried out under greenhouse conditions using a randomized block design in a 4 × 4 factorial scheme corresponding to four levels of electrical conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Hydrogen peroxide is an imperative stress signaling molecule involved in the enhancement of plant growth and development under abiotic stresses (Hossain et al, 2015). This enhancement could be due to improved chlorophyll and gas exchange (Capitulino et al, 2023; Farooq et al, 2017; Iqbal et al, 2018a), which may increase photosynthetic activity, as evident in the present study (Figure 2) and also in line with the findings of Ashraf et al (2015), Guler and Pehlivan (2016), Habib et al (2021), and Iqbal et al (2018b) in maize, soybean, wheat, and quinoa, respectively. In addition, exogenous H 2 O 2 triggers the endogenous concentration of PGRs, such as ABA, GA3, and IAA (Orabi et al, 2015; Terzi et al, 2014), which could be responsible for improved plant growth under drought stress in quinoa (Iqbal et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide is an imperative stress signaling molecule involved in the enhancement of plant growth and development under abiotic stresses (Hossain et al, 2015). This enhancement could be due to improved chlorophyll and gas exchange (Capitulino et al, 2023; Farooq et al, 2017; Iqbal et al, 2018a), which may increase photosynthetic activity, as evident in the present study (Figure 2) and also in line with the findings of Ashraf et al (2015), Guler and Pehlivan (2016), Habib et al (2021), and Iqbal et al (2018b) in maize, soybean, wheat, and quinoa, respectively. In addition, exogenous H 2 O 2 triggers the endogenous concentration of PGRs, such as ABA, GA3, and IAA (Orabi et al, 2015; Terzi et al, 2014), which could be responsible for improved plant growth under drought stress in quinoa (Iqbal et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…According to (Figure 3), the carotenoid content (Carot) decreased by 88.82% in bell pepper plants irrigated with the highest salinity (ECw of 3.1 dS m -1 ) and fertilized with 150% N, showing the lowest estimated mean, 0.43 mg g -1 FM, compared to the bell pepper plants irrigated with low-salinity water and fertilized with 100% N, which showed a mean value of 3.90 mg g -1 FM for this parameter (highest estimated value). Reductions in the carotenoid content caused by salt stress occur due to the degradation of ß-carotene and the reduction in the formation of zeaxanthin due to the increase in reactive oxygen species (ROS), produced at higher amounts when plants are under stress and responsible for enzyme inactivation in plants (Silva et al, 2011;Capitulino et al, 2023). Carotenoids can act as antioxidant agents by protecting lipid membranes from the oxidative stress generated by ROS (Barbosa et al, 2014;Lima et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the beneficial effect of H 2 O 2 at the concentration of 23 µM on NFP may be associated with its function of signaling molecule and protection against biotic and abiotic stresses [36]. Hydrogen peroxide can activate the defense system, contributing to a rapid adaptation of the plant to conditions unfavorable to its development [20,28].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have reported that foliar application of H 2 O 2 can attenuate the deleterious effects caused by salt stress on various vegetables, such as mini watermelon [18], bell peppers [23], melon [24], zucchini [25], and tomatoes [26]. However, it should be considered that the beneficial effects of H 2 O 2 application depend on several factors, including concentration, plant species, development stage, and method of application [27,28].…”
Section: Introductionmentioning
confidence: 99%